2018
DOI: 10.1016/j.jad.2018.08.048
|View full text |Cite
|
Sign up to set email alerts
|

OpenSIMPLe: A real-world implementation feasibility study of a smartphone-based psychoeducation programme for bipolar disorder

Abstract: The 6-month attrition rate of the programme was high. Positive outcomes regarding satisfaction were found predominantly among completers. The optimal dosage and retention of IBP mental health programmes remain challenging issues that need further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 62 publications
2
101
0
1
Order By: Relevance
“…Several studies have demonstrated high rates of user acceptance and satisfaction when using properly tested mental health apps in research studies [8,20,21]. Therefore, there is a need to develop guidelines and frameworks to validate mental health apps in order to make them available to those who might benefit from them [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated high rates of user acceptance and satisfaction when using properly tested mental health apps in research studies [8,20,21]. Therefore, there is a need to develop guidelines and frameworks to validate mental health apps in order to make them available to those who might benefit from them [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already demonstrated the potential for diagnosing and capturing illness activity in BD based on smartphones use patterns [6]. Additionally, these technologies open a two-way avenue to collect a novel type of comprehensive illness-relevant data while simultaneously delivering personalized mental health interventions remotely, at a low cost and on a large scale [7] (Figure 1). Several apps and IBPs have now been developed to deliver psychological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, researchers have found correlations between assessments of psychotic and mood symptoms delivered via smartphone apps and in traditional gold-standard formats [16][17][18]. Additionally, preliminary evidence suggests small improvements in: quality of life and recovery [19]; community functioning [20]; negative symptoms, general psychotic symptoms and mood [21]; positive symptoms, excitement, general psychopathology and disorganisation [22]; and wellbeing [23] after the delivery of DHIs. However, further large-scale studies exploring the specific mechanisms that may elicit change are warranted [20].…”
Section: Introductionmentioning
confidence: 99%
“…26 Although we used a relatively short follow-up period (12 weeks), user engagement with apps is typically higher in the short term and tends to wane over time. For example, the average period of app use is 2 months, 28 and only 27% of participants in another study 29 were still using the app at a 14-week follow-up. We therefore reasoned that we were likely to see greater effects over the short term than long term.…”
Section: A B C Dmentioning
confidence: 99%